2021
DOI: 10.3390/membranes11100724
|View full text |Cite
|
Sign up to set email alerts
|

Fouling Mitigation via Chaotic Advection in a Flat Membrane Module with a Patterned Surface

Abstract: Fouling mitigation using chaotic advection caused by herringbone-shaped grooves in a flat membrane module is numerically investigated. The feed flow is laminar with the Reynolds number (Re) ranging from 50 to 500. In addition, we assume a constant permeate flux on the membrane surface. Typical flow characteristics include two counter-rotating flows and downwelling flows, which are highly influenced by the groove depth at each Re. Poincaré sections are plotted to represent the dynamical systems of the flows and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The performance of a rotary dynamic filtration system is closely related to a secondary flow, such as Taylor vortices created by a high-speed rotation of a rotor, reducing membrane fouling or concentration polarization [ 18 ]. Such a secondary flow in membrane filtration also leads to enhanced mixing and improved fouling resistance via back transport of foulants from the membrane to the bulk flow region [ 27 , 53 ]. In addition, Taylor vortices are also associated with the enhanced shear rate in a dynamic filtration module [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The performance of a rotary dynamic filtration system is closely related to a secondary flow, such as Taylor vortices created by a high-speed rotation of a rotor, reducing membrane fouling or concentration polarization [ 18 ]. Such a secondary flow in membrane filtration also leads to enhanced mixing and improved fouling resistance via back transport of foulants from the membrane to the bulk flow region [ 27 , 53 ]. In addition, Taylor vortices are also associated with the enhanced shear rate in a dynamic filtration module [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…In fluids engineering applications, patterned surfaces are used as a means to add perturbations to a flow field or to guide a flow to a desired direction, where the detailed flows are affected by the topology and the geometrical parameters of a surface pattern [ 44 , 45 , 46 , 47 ]. In membrane filtration, a large number of studies on patterned solid surfaces or patterned membranes are being conducted to elucidate their influences on antifouling and flux enhancement in crossflow filtration [ 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Flow and mass transfer characteristics due to various engineered surface features [ 50 ] and bio-mimetic surface patterns [ 51 ] are main concerns of researchers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jung et al [ 46 ] found that the particles they studied tended to deposit into the surface valleys and not at the peaks, indicating a conclusion later drawn by Jung and Ahn [ 47 ]: a patterned membrane surface can tremendously reduce surface fouling, given a judicious choice in Reynolds number and pattern depth relative to average particle size. Kim et al [ 48 ] recently offered further confirmation of these dependencies via an alternative approach (i.e., a herringbone-patterned mixer to induce chaotic advection in a flat sheet membrane module).…”
Section: Introductionmentioning
confidence: 96%